Study on digital piracy of movies in Western Australia - Liang, Johan (School of Marketing, Curtin Business School, 2010)
This study investigates the personal and social factors influencing "illegal" downloading of movies from the Internet. The data analysis of 203 usable responses indicated three antecedents ("habits", "affect" and "facilitating conditions") have significant relationships with "attitude towards illegally downloading movies". Conversely, "moral judgement", "self efficacy" and "social factors" do not have significant influence towards "attitude towards illegally downloading movies". Additionally, internet usage, internet time spent and internet speed do not have significant influence to respondents' attitude towards illegally downloading movies to change the respondents' intention to download movie illegally in the future. Self-control theory, neutralization theory and theory of planned behaviour are used to explain some of the results. Findings derived from this study can provide useful practical implications for marketers, policy makers and internet gatekeeper to have a better understanding of down-loaders' behaviour and developed better anti-piracy measurements to reduce piracy rate in Australia. The major limitation in this study is the use of a convenience sample from a large university. Further research is needed with a random sample of down-loaders.